Pemanfaatan Tumbuhan Sebagai Media Pembelajaran Herbarium Pada Materi Plantae - Andi Saadillah; Laili Cahyani Sabila; Yuni Isma; Surianti, Surianti; Hamiati, Hamiati; Windi Sasdila; Ruhiba, Ruhiba (Universitas Pahlawan Tuanku Tambusai, 2025)
Teachers are required by the curriculum to be able to design and compile learning models that will be taught to students. The learning model is designed as well as possible so that students are interested and feel happy in participating in learning. One way to do this is by creating creative learning media and being able to involve students directly so that it can develop students' cognitive, affective and psychomotor abilities. By utilizing plants in the environment of SMAS IT Wihdatul Ummah Kolaka and cooperation between students, students, and teachers, these plants can be used as learning media through making herbarium in plantae teaching material in class X SMAS IT Wihdatul Ummah Kolaka. The making of herbarium as a learning medium was carried out by preparing plants as samples in Tahoa Village, Kolaka District, Kolaka Regency, then continued with plant identification at the Sembilanbelas November Kolaka University Laboratory, then the making of herbarium was carried out at SMAS IT Wihdatul Ummah Kolaka. The herbarium that has been made is expected to be able to motivate students in classroom learning and develop student interest, especially in plantae teaching material. This herbarium can also be used as a scientific reference in teaching that can last in the long term.